2010
DOI: 10.1387/ijdb.082772ed
|View full text |Cite
|
Sign up to set email alerts
|

Local regulation of implantation at the human fetal-maternal interface

Abstract: Embryo implantation and formation of a functional placenta are complex processes that require a plethora of regulatory molecules. In recent years, many of these mediators have been identified, often from studies in experimental animals. Furthermore, their expression patterns at the embryo-maternal interface in women have been characterized and provide clues to their potential actions. What has been missing in most cases is any experimental demonstration of their function. Proteases, cytokines and chemokines ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 97 publications
(123 reference statements)
0
69
0
4
Order By: Relevance
“…Most recently, it has been shown that LIF plays a role in both adhesive and invasive phases of implantation owing to its anchoring effect on the trophoblast . 46 These findings suggest that LIF plays a major role in both rodents and primate implantation. Our studies using in vivo human implantation show that an optimum level of LIF is required for blastocyst implantation.…”
Section: Functional Parameter Of Endometrial Receptivitymentioning
confidence: 94%
“…Most recently, it has been shown that LIF plays a role in both adhesive and invasive phases of implantation owing to its anchoring effect on the trophoblast . 46 These findings suggest that LIF plays a major role in both rodents and primate implantation. Our studies using in vivo human implantation show that an optimum level of LIF is required for blastocyst implantation.…”
Section: Functional Parameter Of Endometrial Receptivitymentioning
confidence: 94%
“…LIF is the best example of how hormones act through cytokines in a manner that high levels of estradiol are coincident with upregulation of the uterine LIF during periimplantation period. Most recently, it has been shown that LIF plays a role in both adhesive and invasive phases of implantation due to its anchoring effect on the trophoblast (Dimitriadis et al 2010). These findings suggest that LIF plays a major role in both rodents and primate implantation.…”
Section: Leukemia Inhibitory Factormentioning
confidence: 98%
“…Increased permeability of the uterine vasculature and maturation of the sub-epithelial capillary plexus prepare the vascular network for implantation (Demir et al 2010). This period of w5 days when the decidual reaction begins has been termed the 'window of implantation', and if pregnancy occurs and progesterone levels remain high, the decidua is maintained (Dimitriadis et al 2010b). Decidualisation is a vital process for human pregnancy, functioning to provide maternal immune tolerance, protection of the fetus and to regulate placentation (Salker et al 2010).…”
Section: Endometrial Receptivity and Implantationmentioning
confidence: 99%